Plant Diversity in Sacred Groves of North Gujarat - Mevada, R. J.; Tandel, M. B.; Prajapati, D. R.; Desmukh, H. K.; Prajapati, V. M. (Indian Forester, 2020)
The present study showed the p lant diversity in sacred groves and documentation of the sacred groves in north Gujarat. There were 42 sacred groves documented in different districts ofnorth Gujarat i.e. Banaskantha, Sabarkantha, Dahod and Kachchh, till the date. The number ofspecies in sacred groves was distributed among 51 different families, out ofwhich Mimosaceae family reported a maximum number of species. Out of total 90 species, 62 (68.89%) were trees, 7 (7.78%) shrubs, 15 (16.67%) herbs, 2 (2.22%) grasses and 4 (4.44%) climbers. Considering all the dimensions of sacred groves, it is clear that these are considered as one of the most species-rich areas for plants. This plant diversity is providing multiple uses to local people and plays an important role in conserving the indigenous biodiversity, habitat and ecosystem.